2006
DOI: 10.1093/heapro/dal029
|View full text |Cite
|
Sign up to set email alerts
|

The role of workplace health promotion in addressing job stress

Abstract: The enormous human and economic costs associated with occupational stress suggest that initiatives designed to prevent and/or reduce employee stress should be high on the agenda of workplace health promotion (WHP) programmes. Although employee stress is often the target of WHP, reviews of job stress interventions suggest that the common approach to combating job stress is to focus on the individual without due consideration of the direct impacts of working conditions on health as well as the effects of working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(115 citation statements)
references
References 32 publications
2
103
0
7
Order By: Relevance
“…None of the tested JDCS interaction effects were significant predicators within the given sample of teachers. Previous studies have observed consistent evidence of the main effects of the JDCS work characteristics (Noblet and LaMontagne 2006;Hausser et al, 2010;Luchman and Gonzales-Morales, 2013); however, evidence of their interactive nature of these variables is mixed and observably weak (van der Doef and Maes, 1999;De Lange et al, 2003).…”
Section: The Influence Of Jdcs Work Characteristicsmentioning
confidence: 84%
“…None of the tested JDCS interaction effects were significant predicators within the given sample of teachers. Previous studies have observed consistent evidence of the main effects of the JDCS work characteristics (Noblet and LaMontagne 2006;Hausser et al, 2010;Luchman and Gonzales-Morales, 2013); however, evidence of their interactive nature of these variables is mixed and observably weak (van der Doef and Maes, 1999;De Lange et al, 2003).…”
Section: The Influence Of Jdcs Work Characteristicsmentioning
confidence: 84%
“…Although the impact of job stress on employee well-being and performance is well acknowledged (Bakker et al, 2008;Demerouti et al, 2005) we see that measurement of PSC could provide a useful tool to assist in the change of management practices and in turn worker health and effectiveness. Given that job stress prevention strategies are now becoming more popular in organisations (Noblet & LaMontagne, 2006) and also in Malaysian workplace settings with initiatives from the government to promote healthy working conditions, we consider building a strong PSC may play a key role. Criticisms regarding current practices of job stress prevention suggest that they focus too much on the individual without consideration of working conditions (Noblet & LaMontagne, 2006).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Given that job stress prevention strategies are now becoming more popular in organisations (Noblet & LaMontagne, 2006) and also in Malaysian workplace settings with initiatives from the government to promote healthy working conditions, we consider building a strong PSC may play a key role. Criticisms regarding current practices of job stress prevention suggest that they focus too much on the individual without consideration of working conditions (Noblet & LaMontagne, 2006). We believe that focussing on PSC can remedy this problem.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…75 Although individual-centered approaches may favorably modify behavioral issues such as smoking cessation or sedentary behaviors, they are less likely to reduce workplace stress because they do not address the organization of the workplace management approach. 76 In a systematic review of organizational-level interventions designed to improve employee control, workers experienced health benefits. Egan et al 77 reviewed 18 relevant studies, 11 of which noted improvements in health and none of which reported adverse health effects; however, the authors acknowledged that the organizational interventions were complemented by health education efforts.…”
Section: Stress Management/reductionmentioning
confidence: 99%